2020
DOI: 10.1021/acssensors.0c02016
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity-Improved SERS Detection of Methyltransferase Assisted by Plasmonically Engineered Nanoholes Array and Hybridization Chain Reaction

Abstract: Detection of methyltransferase (MTase) activity is of great significance in methylation-related disease diagnosis and drug screening. Herein, we present a dual-amplification sensing strategy that is assisted by plasmonically enhanced Raman intensity at engineered nanoholes array, along with signal amplification by the hybridization chain reaction (HCR) for the ultrasensitive detection of M.SssI MTase activity and inhibitor screening. An engineered surface-enhanced Raman scattering (SERS) substrate, namely, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The introduction of HCR into SERS-based detection improved the detection sensitivity because it brought more absorbed reporters on the SERS substrate. 36 However, the signal amplification efficiency was weak owing to the near-field effect of SERS enhancement. 37 Some reporter molecules in the chain-like DNA nanostructure located outside of the electromagnetic field (E-field) hardly contribute to the amplified SERS signal.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of HCR into SERS-based detection improved the detection sensitivity because it brought more absorbed reporters on the SERS substrate. 36 However, the signal amplification efficiency was weak owing to the near-field effect of SERS enhancement. 37 Some reporter molecules in the chain-like DNA nanostructure located outside of the electromagnetic field (E-field) hardly contribute to the amplified SERS signal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among these various amplification strategies, HCR is nonenzymatic, simple in design and operation, and cost-effective, making it convenient and the most widely used. The introduction of HCR into SERS-based detection improved the detection sensitivity because it brought more absorbed reporters on the SERS substrate . However, the signal amplification efficiency was weak owing to the near-field effect of SERS enhancement .…”
Section: Introductionmentioning
confidence: 99%
“…111 Luo et al developed a novel SERS strategy at a structured nanohole array with tuned 785 nm surface plasmon resonance (SPR). 112 The substrate exhibited SERS enhancement 500 times higher than that of commercial Klarite substrate, and HCR was further applied for dual amplification for the assay of methyltransferase. Clustered regularly interspaced short palindromic repeats (CRISPR) associated proteins systems have shown great potential in the development of advanced biosensor due to the trans-cleavage capabilities of the Cas effector proteins.…”
Section: Hcr Amplified Signalsmentioning
confidence: 99%
“…With the fingerprint signature and sharp vibrational bands, surface-enhanced Raman scattering (SERS) emerges as an important analytical technique with ultrahigh sensitivity . Luo et al developed a novel SERS strategy at a structured nanohole array with tuned 785 nm surface plasmon resonance (SPR) . The substrate exhibited SERS enhancement 500 times higher than that of commercial Klarite substrate, and HCR was further applied for dual amplification for the assay of methyltransferase.…”
Section: Hcr Amplified Signalsmentioning
confidence: 99%
“…SERS enhancement is dominated by local amplification of the electromagnetic (EM) field . There are several methods to enhance the local EM field, such as the formation of ultrasmall gaps between plasmonic particles or between particles and tips. It has also been reported that such gaps in core–shell structures can give rise to a large SERS enhancement of up to ∼10 11 for embedded Raman labels . These core–shell structures hold great promise for developing broadly applicable SERS tags by incorporating Raman labels as internal standards.…”
Section: Introductionmentioning
confidence: 99%